2020
DOI: 10.20944/preprints202001.0230.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure-Activity Relationship and Mechanistic Insights for Anti-HIV Natural Products

Abstract: Acquired Immunodeficiency Syndrome (AIDS) which is chiefly originated by a retrovirus named Human Immunodeficiency Virus (HIV), has influenced about 70 million populations worldwide. Even though several advancements have been invented in the field of antiretroviral combination therapy, still HIV has become the dominant reason for death in South Africa, for example. The current antiretroviral therapies have achieved success in providing instant HIV suppression but with countless undesirable adverse effects. In … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 165 publications
(187 reference statements)
0
10
0
Order By: Relevance
“…The zinc tetra-ascorbo-camphorate molecule belongs to the heterogenous family of terpenoids, which is abundant, diverse in nature, extracted from various plants or obtained by chemical synthesis, and which comprises several characterized therapeutic agents having a large array of pharmacological properties such as anticancer, analgesic, anti-inflammatory, immunomodulatory, and antiviral activities [ 11 , 15 , 16 ]. Antiviral activities of terpenoids have been reported for a wide variety of RNA and DNA viruses, including HIV [ 11 , 16 , 17 , 27 , 28 ], influenza virus A/WSN/33 (H1N1) [ 29 ], or other influenza viruses [ 15 ], hepatitis A virus [ 15 , 30 ], hepatitis B virus [ 12 , 15 , 31 , 32 ], hepatitis C virus [ 15 , 33 ], vesicular stomatitis virus [ 15 ], human enterovirus 71 [ 15 ], orthopoxviruses [ 34 ] pathogenic flaviviruses [ 35 ] including dengue virus [ 36 ], Herpesviridae family viruses [varicella-zoster virus, herpes simplex virus type (HSV) type 1 (HSV-1), Epstein-Barr virus, cytomegalovirus] [ 15 , 31 , 33 , 37 , 38 ] and emerging pathogenic SARS-coronaviruses [ 15 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The zinc tetra-ascorbo-camphorate molecule belongs to the heterogenous family of terpenoids, which is abundant, diverse in nature, extracted from various plants or obtained by chemical synthesis, and which comprises several characterized therapeutic agents having a large array of pharmacological properties such as anticancer, analgesic, anti-inflammatory, immunomodulatory, and antiviral activities [ 11 , 15 , 16 ]. Antiviral activities of terpenoids have been reported for a wide variety of RNA and DNA viruses, including HIV [ 11 , 16 , 17 , 27 , 28 ], influenza virus A/WSN/33 (H1N1) [ 29 ], or other influenza viruses [ 15 ], hepatitis A virus [ 15 , 30 ], hepatitis B virus [ 12 , 15 , 31 , 32 ], hepatitis C virus [ 15 , 33 ], vesicular stomatitis virus [ 15 ], human enterovirus 71 [ 15 ], orthopoxviruses [ 34 ] pathogenic flaviviruses [ 35 ] including dengue virus [ 36 ], Herpesviridae family viruses [varicella-zoster virus, herpes simplex virus type (HSV) type 1 (HSV-1), Epstein-Barr virus, cytomegalovirus] [ 15 , 31 , 33 , 37 , 38 ] and emerging pathogenic SARS-coronaviruses [ 15 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products constitute a wide source of antiviral agents, a priori devoid of cellular toxicity [ 11 ]. Terpenoids, which derive from isoprene (C 5 H 8 ) with a great diversity of chemical structure, are abundant plant metabolites, several molecules of which have therapeutic, anti-tumor and anti-inflammatory properties [ 12 , 13 , 14 , 15 , 16 ]. Furthermore, terpenoids have generated a lot of interest due to their antiviral properties in vitro against HIV [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the failure of existing anti-AIDS techniques due to multidrug resistance, most treatment plans look to natural items with anti-HIV potential [ 92 ]. This necessitates the development of novel and effective anti-AIDS medications derived from natural sources [ 92 ].…”
Section: Inos and Cox-2 Enzymes Overexpressionmentioning
confidence: 99%
“…As a result of the failure of existing anti-AIDS techniques due to multidrug resistance, most treatment plans look to natural items with anti-HIV potential [ 92 ]. This necessitates the development of novel and effective anti-AIDS medications derived from natural sources [ 92 ]. WHO proposes that ethnomedicines and several other natural elements be thoroughly tested to achieve the goal of preventing HIV [ 93 , 94 ].…”
Section: Inos and Cox-2 Enzymes Overexpressionmentioning
confidence: 99%
“…Review articles in this SI discuss recent studies that attempt to investigate the SAR of NPs that have shown anti-HIV activities [ 28 ], modulatory activities in zinc-independent histone deacetylases, sirtuins often implicated in human disease [ 29 ] and SAR in plant-derived sweeteners [ 30 ]. The readers are invited to enjoy the reading of the articles of this SI.…”
mentioning
confidence: 99%